2021
DOI: 10.1093/bib/bbab291
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of molecular fingerprints in prediction of drug combination effects

Abstract: Application of machine and deep learning methods in drug discovery and cancer research has gained a considerable amount of attention in the past years. As the field grows, it becomes crucial to systematically evaluate the performance of novel computational solutions in relation to established techniques. To this end, we compare rule-based and data-driven molecular representations in prediction of drug combination sensitivity and drug synergy scores using standardized results of 14 high-throughput screening stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 98 publications
(71 reference statements)
0
48
0
Order By: Relevance
“…7,[19][20][21] Previous reports vary in their conclusions on whether the implementation of chemical descriptors, rather than generic one-hot encoding (OHE) representations, truly boosted the predictive performance of their ML models. 19,22,23 Pdcatalyzed C(sp 3 )-H activation is a powerful reaction manifold that enables the facile introduction of functional complexity in small molecules, in addition to the late-stage functionalization of complex molecules like trimipramine (1), a tricyclic antidepressant, as recently demonstrated by one of our groups. 24 Hence we chose to explore the parameterization and featurization of the newly developed tertiary amine directed C(sp 3 )-H bond activation with a HTE-generated dataset, comparing tailored descriptors, based on in silico studies, to understand the influence of descriptor complexity on supervised ML prediction and closed-loop optimization.…”
Section: Introductionmentioning
confidence: 99%
“…7,[19][20][21] Previous reports vary in their conclusions on whether the implementation of chemical descriptors, rather than generic one-hot encoding (OHE) representations, truly boosted the predictive performance of their ML models. 19,22,23 Pdcatalyzed C(sp 3 )-H activation is a powerful reaction manifold that enables the facile introduction of functional complexity in small molecules, in addition to the late-stage functionalization of complex molecules like trimipramine (1), a tricyclic antidepressant, as recently demonstrated by one of our groups. 24 Hence we chose to explore the parameterization and featurization of the newly developed tertiary amine directed C(sp 3 )-H bond activation with a HTE-generated dataset, comparing tailored descriptors, based on in silico studies, to understand the influence of descriptor complexity on supervised ML prediction and closed-loop optimization.…”
Section: Introductionmentioning
confidence: 99%
“…This makes it a powerful 2/22 approach to develop models that are able to predict drug synergy based on drug combination screening experiments and other relevant data. Several ML models for drug synergy prediction have been described in the literature [8,[11][12][13][14][15]. Many of these studies used tree-based ML methods, such as random forests (RFs) [11,12,14] or gradient boosting [12,13,15].…”
Section: Introductionmentioning
confidence: 99%
“…Given that the screening datasets that are currently available only contain a very limited number of compounds, it is still unclear whether there is any benefit in using learned representations instead of traditional fingerprints and descriptors. A recent study benchmarked several compound representations on a large drug synergy dataset and found that DL-based representations were able to outperform traditional fingerprints [15]. However, the authors also noted that the difference between the top performing DL-based methods and the best fingerprints was not substantial and that other concerns, such as interpretability, may be more important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research [13] proposed a method called DeepConv-DTI that applies convolutional neural network (CNN) in predicting binary classification DTI using amino acid composition (AAC) as protein features and circular fingerprints as compound features by analyzing compound's molecule as a graph. Choosing the right type of fingerprint to represent the features of the compound is important in the process of searching for potential drugs [14].…”
Section: Introductionmentioning
confidence: 99%